Photo art creativity in the education light drawing - Acar, Hacı Mehmet; Kavuran, Tamer (My University, 2016)
Since the early ages, people live together with art, and create various branches of art. Painting, as one of the most important branches of art, occurs on the walls of the caves of prehistoric ages. By the nineteenth century, photography shows itself and come as a branch of art until today. Photographers have created new methods and techniques throughout history. Among these, we can say that “painting with light” is one of the techniques by which the artist can create original works of art and reflects his/her creativity freely. This study aims to cite the importance of creativity in art education by the applications of “painting with light”. First the history of art is touched briefly, and then the invention of photography is mentioned and the relationships of photography and painting is studied. In the final section by informing about the technique of “painting with light”, it is discoursed how to get a work of art with this technique.
Bildiri - Yayımlanmış
DOI: 10.1051/shsconf/20162601083
Keywords: Photograph; Ight drawing; Art; Creativity